The Effect of Compress Kol (Brassica Oleracea Var. Capitata) and Warm Compression On The Pain of Breast Swallowing In Post Partum Women In The Teratai Room Arifin Achmad Hospital, Riau Province - ., Meriani; Laila, Ani; ., Yanti (JURNAL IBU DAN ANAK, 2020)
Abstract 2Breastfeeding problems that can arise during the postpartum period arebreast engorgement pain. The pain in the breast can make the mother andbaby feel uncomfortable. Non-pharmacological methods that can be used toreduce the pain of swelling of the breast are cabbage compresses and warmcompresses. The purpose of this study is to determine The effect of cabbagecompresses and warm compresses to reduce pain intensity in breastengorgement. The study was conducted in March 2019 - June 2019 in theTeratai Room of Arifin Achmad Hospital, Riau Province. This type of researchis quasi-experimental with a pretest-posttest two group design. post partumwhich was treated in the Teratai Room of the Arifin Achmad Hospital, RiaudProvince with a sample of 10 respondents in the cabbage compress groupand 10 respondents in the warm compress group who were taken bypurposive sampling technique. Collecting data using an observation sheetcontaining a pain scale Numeric Rating Scale (NRS). The results showed thatthe average pain intensity before the cabbage compress and before thewarm compress was 5.7 (SD 1.34) and after being given treatment the resultswere obtained on the cabbage compress 2. , 9 (SD 1.10) and warmcompresses 4.1 (SD 1.28). The results of statistical tests showed that there wasa difference in the pain intensity of breast swelling after being treatedbetween hot compresses and warm compresses in the Teratai room of ArifinAchmad Hospital, Riau Province (p = 0.042), cabbage compresses were moreeffective in reducing pain than warm compresses. It is suggested to themanagement of Arifin Achmad Hospital to consider giving cabbagecompresses as an effective and economical non-pharmacological method inreducing the pain of breast swelling in post partum mothers.